Toxicity of fresh and dried neem seed extracts against golden apple snail, pomacea canaliculate / Mohd Fahmi Keni - Keni, Mohd Fahmi (2018)
The golden apple snail, Pomacea canaliculata is an invasive alien species that seriously affects rice cultivation in many Asian countries. These freshwater mollusc devour young rice seedlings, causing extensive damage to both transplanted and direct seedling. Most Asian farmers resort to short-term solutions by using molluscicides that have negative impacts on non-target organisms, aquatic biodiversity, and the environment. Due to the toxic hazards of the synthetic insecticides, biological control through botanical pesticides is the best alternative for reducing the golden apple snail damage in paddy fields. Neem or also known as Azadiractha indica was proven to have the molluscicidal potential for controlling golden apple snails. The purposes of this study were to determine toxicity of different neem seed extracts for controlling golden apple snail and also to identify the antifeedent activity of different neem extract for controlling golden apple snail. Azadirachtin content was quantified using spectrophotometer. Bioassay and antifeedant test was conducted with five different concentration of neem seed extract. The mortality golden apple snail increased with increasing concentration of extract 100,000 ppm to 500,000 ppm and exposure time from 24 to 96 hours. The methanol extraction with dried neem seed (LCso= 180,590 ppm) showed high mortality rate compared to the fresh neem seed extract (LC50 = 267,960 ppm). Meanwhile, water extraction with fresh neem seed (LC50 = 248,880 ppm) showed high mortality rate compared with the dried neem seed extract (LC50 = 388,320 ppm). Methanol extraction with fresh neem seed showed high antifeedant activities compared with other treatments with 81% feeding deterrent index (FDI). Azadirachtin content in the neem seed extract showed in range 53.36 to 54.08 ppm for methanol extraction and 52.95 to 53.97 ppm for water extraction. Methanol extraction with dried neem seed showed high mortality and antifeedant activity towards golden apple snajl compared with fresh neem seed. Meanwhile, water extraction with fresh neem seed showed high mortality and antifeedant activity compared dried neem seed. Based on the finding, the neem seed has potential to be formulated as biopesticide for management of golden apple snail in the field. For further study, application of neem in real situation in the paddy field should be done to determine the effect of the neem extracts under different environmental situation.